Еvaluation of the development strategy of the hotel and restaurant industry of Ukraine - Olha Nikolaichuk (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
In modern conditions, the development of the domestic hotel and restaurant industry is accompanied by significant problems caused by the COVID-19 pandemic and the full-scale war with the Russian Federation, which necessitates the search for promising directions of development and the development of plans for its recovery in the post-war period. The subject of research in the article is the development strategy of the hotel and restaurant industry of Ukraine. The purpose of the article is assessment of the strategy for the development of the hotel and restaurant industry of Ukraine and its infrastructure on this basis of the approach to the implementation of the strategy for the development of galusia in the minds of military renewal. Research methods: dialectical method, fundamental scientific methods: analysis, synthesis, taxonomic analysis, systematization, formalization (for analysis of the research object), abstract-logical method (for formulating concepts), graphical and tabular methods (for analysis of the results of the investigation). The following results were obtained: A model of taxonomic analysis of the development strategy of the hotel and restaurant industry is proposed. The taxonomic coefficients of the development strategy of the hotel and restaurant industry of Ukraine have been determined. Cyclicality in the development of the hotel and restaurant industry of Ukraine has been recorded. Especially negative changes in the industry were recorded in 2022 as a result of a full-scale.  Conclusions: the conducted research made it possible to propose strategic directions for the development of the hotel and restaurant industry of Ukraine in the post-war period. The above-mentioned measures will make it possible to implement the necessary strategic changes in the hotel and restaurant industry, will contribute to the reconstruction of the national economy and the generation of additional financial flows, which will make it possible to strengthen the impact of industry restoration projects on the socio-economic development of the state.